Optimisation of age at first calving in Karan Fries cattle - JAPHETH, K PUHLE; MEHLA, R K; LATHWAL, S S; NARWARIA, U S; MAHER, DINESH M; BHARTI, PRANAY (The Indian Journal of Animal Sciences, 2016)
The study was conducted on the performance records of age at first calving (AFC) spread over a period of 15 years on Karan Fries crossbred cattle maintained at Livestock Research Centre. Data of 676 cows were collected and analysed by Least Squares Technique to examine the effect of non-genetic factors on age at first calving. Period of birth was classified into 5 periods (I-V) and season of calving into 4 seasons (winter, summer, rainy and autumn) to see the effect of non-genetic factors on age at first calving. Effect of period of birth was significant on age at first calving while season of calving showed non-significant effect on age at first calving. The overall least squares mean of age at first calving was 1043.40±6.64 days. For the optimisation of age at first calving with regard to milk productivity, analysis was carried out by class interval method. Age at first calving was classified into 7 classes and its average means of milk yield were obtained by using Least Squares Technique where optimum level of age at first calving was obtained at 885–1100 days based on higher milk yield and numbers of animal observed in different classes. From the study, it was concluded that optimum age at first calving could be achieved through proper nutrition and management practices. However, to determine the optimum level of age at first calving, much emphasis should be given to maximum profit rather than maximizing milk production.